Business and Social Science Students’ Course Preferences and Learning Approaches - Halme, Merja; Myyry, Liisa; Pirttilä-Backman, Anna-Maija (Frontiers in Education, 2021)
The study examines university students’ course preferences and their relations to learning approaches, apparently for the first time, to gain insight how course design is experienced by students. The data includes students from two fields: business (n=467) and social sciences (n=313). The attributes in preference measurement were selected on the basis of focus groups discussions and choice-based conjoint analysis was used. The learning approaches were measured using Experiences of Teaching and Learning Questionnaire developed by Entwistle and Ramsden. Social science students valued more interesting, challenging and time-consuming courses than business students, who valued more relevant and easier courses requiring less time. Social science students scored higher in the deep approach. The relationship between preferences and approaches was strikingly similar in the two universities: strategic students prefer relevance and deep learners challenge in both universities. An exception was that interesting courses were related to deep learning among social science students, and to the surface approach among business students. Further studies should extend our understanding of what interesting means to different kinds of students. The results give tools to design courses that enhance students’ learning and offers new insights to learning approach research.